Tinjauan Yuridis Sengketa Peralihan Hak Atas Tanah Hibah Ditinjau Berdasarkan Peraturan Perundang-Undangan - Afrizal Pramudito, Muhammad; Djayaputra, Gunawan (Universitas Ekasakti, 2023)
Soil is a source of life not only for humans but for every living creature on earth such as animals and plants. In the Civil Code, land is categorized as immovable objects in accordance with Article 506 of the Civil Code. The transfer of land rights in the form of a grant is often a problem in people's lives. The definition of a gift is regulated in Article 1666 of the Civil Code, namely: